Activated Notch4 Inhibits Angiogenesis: Role of β1-Integrin Activation - Leong, Kevin G. (American Society for Microbiology, 2002)
Notch4 is a member of the Notch family of transmembrane receptors that is expressed primarily on endothelial cells. Activation of Notch in various cell systems has been shown to regulate cell fate decisions. The sprouting of endothelial cells from microvessels, or angiogenesis, involves the modulation of the endothelial cell phenotype. Based on the function of other Notch family members and the expression pattern of Notch4, we postulated that Notch4 activation would modulate angiogenesis. Using an in vitro endothelial-sprouting assay, we show that expression of constitutively active Notch4 in human dermal microvascular endothelial cells (HMEC-1) inhibits endothelial sprouting. We also show that activated Notch4 inhibits vascular endothelial growth factor (VEGF)-induced angiogenesis in the chick chorioallantoic membrane in vivo. Activated Notch4 does not inhibit HMEC-1 proliferation or migration through fibrinogen. However, migration through collagen is inhibited. Our data show that Notch4 cells exhibit increased β1-integrin-mediated adhesion to collagen. HMEC-1 expressing activated Notch4 do not have increased surface expression of β1-integrins. Rather, we demonstrate that Notch4-expressing cells display β1-integrin in an active, high-affinity conformation. Furthermore, using function-activating β1-integrin antibodies, we demonstrate that activation of β1-integrins is sufficient to inhibit VEGF-induced endothelial sprouting in vitro and angiogenesis in vivo. Our findings suggest that constitutive Notch4 activation in endothelial cells inhibits angiogenesis in part by promoting β1-integrin-mediated adhesion to the underlying matrix.